Advance on processing of compostable and thermally stable biodegradable polyester blends. Issue 21 (26th November 2019) - Barletta, Massimiliano; Aversa, C.; Pizzi, E.; Puopolo, M.
ABSTRACT: Flexible and semiflexible packagings can be manufactured by cast extrusion of plastic sheet and thermoforming of containers. Thermal stability is often required as packaging items after being thermoformed can come in contact with hot food/beverage, especially during hot filling operations. In this framework, the present study deals with the design and manufacturing by thermoforming of plastic containers that are, at the same time, compostable and suitable for high‐temperature applications (~100 °C). First, extrusion compounding of Poly(l ‐lactic acid) (PLLA)‐based biodegradable polyester blends was performed. In particular, the effect on the material properties of different types of nucleating agents was investigated. Combinations of micro‐lamellar talc, poly(d ‐lactic acid) (PDLA), ethylene bisstearamide (EBS), and titanium dioxide (TiO2 ) were studied. The formulations involving EBS boast the highest crystallinity and the fastest onset of the crystalline phase on sheets produced by cast extrusion. Conversely, the formulations involving TiO2 feature the lowest degree of crystallinity and the slowest onset of the crystalline phase. Combinations of talc and PDLA exhibit an intermediate behavior. Second, thermoforming of the plastic foils was performed. A very different trend of the crystallization after thermoforming is shown. Indeed, crystallinity is the highest for the formulations involving talc and PDLA, the lowest for the ones containing EBS. In conclusion, the biodegradable polyester blends are found to be suitable for the manufacturing of compostable and thermostable packaging items by cast extrusion and thermoforming. Final crystallization of the material and the resulting thermal stability can be fine‐tuned by modulating type and amount of nucleating agents. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48722. Abstract :